Evidence of the complexity of aerosol transport in the lower troposphere on the Namibian coast during AEROCLO-sA - P. Chazette; C. Flamant; J. Totems; M. Gaetani; M. Gaetani; G. Smith; G. Smith; A. Baron; X. Landsheere; K. Desboeufs; J.-F. Doussin; P. Formenti (Atmospheric Chemistry and Physics, 2019)
The evolution of the vertical distribution and optical properties of aerosols in the free troposphere, above stratocumulus, is characterized for the first time over the Namibian coast, a region where uncertainties on aerosol–cloud coupling in climate simulations are significant. We show the high variability of atmospheric aerosol composition in the lower and middle troposphere during the Aerosols, Radiation and Clouds in southern Africa (AEROCLO-sA) field campaign (22 August–12 September 2017) around the Henties Bay supersite using a combination of ground-based, airborne and space-borne lidar measurements. Three distinct periods of 4 to 7 d are observed, associated with increasing aerosol loads (aerosol optical thickness at 550 nm ranging from ∼0.2 to ∼0.7), as well as increasing lofted aerosol layer depth and top altitude. Aerosols are observed up to 6 km above mean sea level during the later period. Aerosols transported within the free troposphere are mainly polluted dust (predominantly dust mixed with smoke from fires) for the first two periods (22 August–1 September 2017) and smoke for the last part (3–9 September) of the field campaign. As shown by Lagrangian back-trajectory analyses, the main contribution to the aerosol optical thickness over Henties Bay is shown to be due to biomass burning over Angola. Nevertheless, in early September, the highest aerosol layers (between 5 and 6 km above mean sea level) seem to come from South America (southern Brazil, Argentina and Uruguay) and reach Henties Bay after 3 to 6 d. Aerosols appear to be transported eastward by the midlatitude westerlies and towards southern Africa by the equatorward moving cut-off low originating from within the westerlies. All the observations show a very complex mixture of aerosols over the coastal regions of Namibia that must be taken into account when investigating aerosol radiative effects above stratocumulus clouds in the southeast Atlantic Ocean.